ANALYSIS OF THE EFFECT OF GOVERNMENT ROLE AND SOCIAL CAPITAL IN DISASTER MANAGEMENT ON ECONOMIC RECOVERY OF DISASTER VICTIMS IN THE SARBAGITA AREA OF BALI PROVINCE - Usadhi P.A.W.; Sudibia I K. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
Disaster management as part of development requires the common perception of various actors and the integration of its implementation to get results that are right on target, effective, efficient and sustainable, especially in efforts to accelerate the economic recovery of disaster victims. This research was conducted in the Denpasar, Badung and Gianyar regions of Bali Province to analyze the influence of the role of government, social capital and disaster management in the economic recovery of disaster victims. The results of the study show that the role of government and social capital has a positive and significant effect on disaster management. The role of government and social capital in disaster management has a significant effect on economic recovery. The government needs to conduct a more comprehensive study in determining strategies and policies in the field of disaster management and increasing mutual trust between communities and the government. The construction of an early warning system and physical infrastructure need to more concern because the success of the economic recovery program is inseparable from disaster risk reduction efforts.